Improving the Eight-One Grade Students’ Achievement on Reading Comprehension Through Jigsaw Model at SMP Negeri 3 Banyuasin I - Azalal Mawardi (ELTE Journal (English Languange Teaching and Education), 2013)
Abstract This research study was conducted based on the problem faced by the writer as a teacher of English at SMP Negeri 3 Banyuasin I. The result of the preliminary study indicated that the eighth-one grade students achievement on reading comprehension could not fulfill the standard criteria of success. This study was the classroom action research which conducted in three cycles. Each cycle consisted planning, action, observation, reflection. In each cycle had twomeetings for treatment, and one meeting for test. There were 40 students as the subject of this research. The data of this study consisted of quantitative and qualitative, the quantitative data were obtained from tests, while qualitative data were taken from the observation result. Based on the result of the test and observation in the third cycle, the writer drew a conclusion that jigsaw model could improve the students’ reading comprehension achievement of the Eighth-One Grade Students of SMP Negeri 3 Banyuasin I in Academin Year 2012/2013. The improvement was shown in the result of the test and the activities during teaching and learning process of reading comprehension in cycle III. The percentage for classical achievement of the students who could fulfill the success criteria was increasing, there were 35 students or 87.50%, and the percentage of inactive students decreased in cycle III, it was only 6 students or 15 %.Keywords : Jigsaw Model, Reading Comprehension Achievement